2020
DOI: 10.1186/s40658-020-0270-y
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructed spatial resolution and contrast recovery with Bayesian penalized likelihood reconstruction (Q.Clear) for FDG-PET compared to time-of-flight (TOF) with point spread function (PSF)

Abstract: Background: Bayesian penalized likelihood reconstruction for PET (e.g., GE Q.Clear) aims at improving convergence of lesion activity while ensuring sufficient signal-tonoise ratio (SNR). This study evaluated reconstructed spatial resolution, maximum/ peak contrast recovery (CRmax/CRpeak) and SNR of Q.Clear compared to time-offlight (TOF) OSEM with and without point spread function (PSF) modeling. Methods: The NEMA IEC Body phantom was scanned five times (3 min scan duration, 30 min between scans, background, 1… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
55
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
3

Relationship

3
7

Authors

Journals

citations
Cited by 51 publications
(64 citation statements)
references
References 19 publications
2
55
0
5
Order By: Relevance
“…The RC increased as a function of decreasing β values as well as with the increasing sphere diameter. The RC is benefited for higher spatial resolution, and Rogasch et al reported that the spatial resolution of BPL at a lower β value was significantly better than that of OSEM [35]. We considered that the increasing RC is mainly due to the effect of the edge-preserving properties of the relative difference penalty (RDP) in BPL reconstruction at lower β values, which γ in RDP is a parameter that controls the degree of edge-preservation [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…The RC increased as a function of decreasing β values as well as with the increasing sphere diameter. The RC is benefited for higher spatial resolution, and Rogasch et al reported that the spatial resolution of BPL at a lower β value was significantly better than that of OSEM [35]. We considered that the increasing RC is mainly due to the effect of the edge-preserving properties of the relative difference penalty (RDP) in BPL reconstruction at lower β values, which γ in RDP is a parameter that controls the degree of edge-preservation [36,37].…”
Section: Discussionmentioning
confidence: 99%
“…This partly explains high inter-method differences, which exceeded 100% for TOF 4/8 and TOF 4/16 (Table 2 ), and frequent discordant cases even if pairs of algorithms with 5 versus 5 mm FWHM were compared. In addition to higher noise, Gibbs artifacts (edge elevations) caused by PSF + TOF and Q.Clear reconstruction increase with narrower in-plane filters or lower β [ 40 ]. Consequently, SUVmax differences will be more prominent than at 7 mm or 9 mm FWHM.…”
Section: Discussionmentioning
confidence: 99%
“…1) which partly explains high inter-method differences and discordant cases even if pairs of algorithms with 5 vs. 5 mm FWHM were compared. In addition to higher noise, Gibbs artifacts (edge elevations) caused by PSF + TOF and Q.Clear reconstruction increase with narrower in-plane lters or lower β (30). Consequently, SUVmax differences will be more prominent than at 7 mm or 9 mm FWHM.…”
Section: Discussionmentioning
confidence: 99%